2006
DOI: 10.1111/j.1365-2125.2006.02597.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Safety and efficacy of tramadol in the treatment of idiopathic detrusor overactivity: a double‐blind, placebo‐controlled, randomized study

Abstract: AimTo evaluate the efficacy and safety of tramadol in patients with idiopathic detrusor overactivity (IDO). MethodsA total of 76 patients 18 years or older with IDO were randomly assigned to receive 100 mg tramadol sustained release (group 1, n = 38) or placebo (group 2, n = 38) every 12 h for 12 weeks. Clinical evaluation was performed at baseline and every 2 weeks during treatment. All patients underwent urodynamics and ice water test at baseline and 12-week treatment. Main outcome measures were number of vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 33 publications
(84 reference statements)
0
21
0
Order By: Relevance
“…Singh et al [2008] gave tramadol epidurally and found the drug to increase bladder capacity and compliance, and to delay filling sensations without ill effects on voiding. Safarinejad and Hosseini [2006] evaluated in a double-blind placebo-controlled randomized study, the efficacy and safety of tramadol in patients with idiopathic DO. A total of 76 patients 18 years of age or older were given 100 mg tramadol sustained release every 12 h for 12 weeks.…”
Section: Tramadolmentioning
confidence: 99%
“…Singh et al [2008] gave tramadol epidurally and found the drug to increase bladder capacity and compliance, and to delay filling sensations without ill effects on voiding. Safarinejad and Hosseini [2006] evaluated in a double-blind placebo-controlled randomized study, the efficacy and safety of tramadol in patients with idiopathic DO. A total of 76 patients 18 years of age or older were given 100 mg tramadol sustained release every 12 h for 12 weeks.…”
Section: Tramadolmentioning
confidence: 99%
“…207 Tramadol also inhibited DO induced by apomorphine in rats-a model of bladder dysfunction in Parkinson's disease. 208 In a double-blind, placebo-controlled, randomized study, Safarinejad and Hosseini 209 evaluated the efficacy and safety of tramadol in patients with idiopathic DO. A total of 76 patients !18 years old were given 100 mg tramadol sustained release every 12 hr for 12 weeks.…”
Section: Targets Within the Central Nervous System (Cns)mentioning
confidence: 99%
“…Substance P has a specific receptor (NK1) that is expressed in the dorsal horn of the spinal cord and may play an important role in detrusor overactivity. (Grond & Sablotzki, 2004;Safarinejad & Hosseini, 2006) Aprepitant, an NK1 receptor antagonist, has been shown to significantly improve symptoms of OAB in postmenopausal women with a history of urgency incontinence or mixed incontinence in a small pilot. (Green et al, 2006) Aprepitant significantly decreased the average daily number of micturitions (−1.3 ± 1.9) compared with placebo (−0.4 ± 1.7).…”
Section: Tachykininsmentioning
confidence: 99%
“…(Andersson & Pehrson, 2003) Tramadol is an analgesic that is a weak μ-receptor agonist; however, it is metabolized to several different compounds, which inhibit serotonin (5-HT) and noradrenaline reuptake. (Grond & Sablotzki, 2004;Safarinejad & Hosseini, 2006) Both μ-receptor agonist and amine reuptake inhibition are useful in the treatment of OAB. In a double-blind, placebo-controlled, randomized study, 76 patients were given 100 mg tramadol sustained release every 12 hours for 12 weeks.…”
Section: Tramadolmentioning
confidence: 99%